2012
DOI: 10.1210/jc.2012-2390
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Clinical Significance of F-18-FDG-PET/CT Thyroid Incidentalomas

Abstract: F-18-FDG-PET/CT thyroid incidentaloma is a relevant clinical finding; diffuse uptakes and most focal uptakes are commonly caused by benign diseases, whereas about one third of focal uptakes are malignant; the most frequent malignant histological type responsible for F-18-FDG-PET/CT thyroid incidentaloma is papillary thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 66 publications
15
110
2
6
Order By: Relevance
“…By contrast, as expected, we found a low PPV of 18 F-FDG PET/CT (38%) confirming previous data (23,24). All in all, a negative 18 F-FDG PET/CT significantly reduces inappropriate thyroidectomies while positive nodules deserve lobectomy and histological examination.…”
Section: F-fdg Pet/ct Mpus and 99msupporting
confidence: 91%
“…By contrast, as expected, we found a low PPV of 18 F-FDG PET/CT (38%) confirming previous data (23,24). All in all, a negative 18 F-FDG PET/CT significantly reduces inappropriate thyroidectomies while positive nodules deserve lobectomy and histological examination.…”
Section: F-fdg Pet/ct Mpus and 99msupporting
confidence: 91%
“…These facts have relevance in terms of imaging diagnosis. Imaging by FDG-PET has the potential to reveal unsuspected tumours, including thyroid tumours, commonly indicated as 'incidentaloma' because of their accidental discovery (Bogsrud et al 2010, Hsiao et al 2011, Pagano et al 2011, Bertagna et al 2012. Novel non-radioactive methods for imaging the glucose internalisation by cancer cells are being developed (Walker-Samuel et al 2013), underscoring the importance of glucose uptake as a diagnostic readout of cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A proportion meta-analysis performed by Bertagna et al (92) with a total of 147 505 subjects from 27 studies revealed a pooled incidence and a malignancy ratio of 2.46% (95% CI 1.68, 3.39%) and 34.6% (95% CI 29.3, 40.2%) respectively. Soelberg et al (91) calculated the prevalence and the risk of malignancy of thyroid incidentalomas reported in 22 selected studies involving 125 754 subjects.…”
Section: Clinical Significance Of Thyroid Pet Incidentalomamentioning
confidence: 99%
“…These studies show that the incidence of thyroid incidentalomas, although low as a percentage, is not negligible, and that about one-third of clinically asymptomatic patients would have had a late diagnosis of thyroid cancer had they not undergone a PET scan. In these cases, the most frequent malignant histological type that was responsible for FDG-PET/CT thyroid incidentaloma was papillary thyroid cancer, and there is no safe SUV cutoff for which it is certain or reasonably safe to either suspect or rule out malignancies (92).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%